Draft Annual Plan 1987-88 Seventh Five Year Plan 1985-90 Scheme-Wise Details Union Territory of Pondicherry - Planning Commission (Planning Commission, 1985)
The Union Territory of Pondicherry consists of four regions, nearly, Pondicherry, Karaikal, Mahe and Yanam lying Graphically isolated from one another. Pondicherry region which is on the cast coast, about 160 Kms. south of Madras is the largest of these and consists of 12 scatter, areas interspersed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is about 1 40 Kms* south of Pondicherry and it is surrounded by Thanjavur district of Tamilnadu. Yanam region is located about 65C Kms, north of Madras near Kakinada in Andhra Pradesh. Mahe region is on the west coast near Pondicherry in Kerala.
Government of Pondicherry, Planning and Research Department